Biotransformation of grape pomace from Vitis labrusca by Peniophora albobadia LPSC # 285 (Basidiomycota) - TRONCOZO,MARÍA I. (2020)
Abstract Grape pomace from Vitis labrusca is an important sub-product of the “American table wine” industry. It is recalcitrant to degradation, and its accumulation is a serious problem with negative environmental impacts. We analyzed the ability of five white-rot fungi to transform this residue in-vitro. Mass loss and phenol removal in grape pomace treated with each fungus were compared after 30-day solid-state fermentation. Since Peniophora albobadia isolate LPSC 285 was the fungus that showed the highest degradative ability and the lowest free phenol levels in the residue transformed, we selected this fungus to monitor its effect on this residue after 30, 60, and 90 days of incubation. We analyzed mass loss of the residue caused by the fungus activity and its chemical changes using Fourier transform infrared spectroscopy. After 90 days of incubation, Peniophora albobadia isolate LPSC 285 reduced grape pomace mass by 20.48%, which was associated with degradation of polysaccharides and aromatic structures. We concluded that Peniophora albobadia LPSC # 285 isolate is a promising fungus to transform grape pomace from Vitis labrusca under solid-state fermentation conditions.